Lower Limb Skeletal Robustness Determines the Change of Directional Speed Performance in Youth Ice Hockey - Slavicek, Tobias; Stastny, Petr; Roczniok, Robert; Musalek, Martin (Journal of human kinetics, 2022)
The factors that influence the on-ice change of directional speed (COD) of ice hockey players remain unclear. Therefore, this study aimed to determine which off-ice and anthropometric variables determine hockey COD with and without a puck. Thirty-two elite ice hockey players (age: 17.64 ± 1.02 years, body height: 180 ± 7.5 cm, body mass: 76.4 ± 7.8 kg) performed squat jumps, broad jumps, countermovement jumps, and pull-ups and were assessed on agility office and on-ice, with and without a puck. Anthropometric characteristics were determined according to the modified somatotype method. A moderate correlation (r = 0.59-0.6) was observed among all agility tests, between on-ice agility with a puck and lower limb skeletal robustness (r = 0.45), and between on-ice agility with a puck and sit-and-reach scores (r = -0.50). Agility without a puck correlated with squat jump height (r = -0.36). Multiple regression analysis indicated that off-ice agility (β = 0.51) and skeletal robustness of the lower limbs (β = 0.35) determined (R2 = 0.41) on-ice agility with a puck. Players' COD was assessed by Illinois tests of agility off-ice and on-ice, with and without a puck; each of these tests moderately predicted the others, but differed in their physical constraints. Players with higher skeletal robustness used more strength and power to achieve COD performance, while players with lower skeletal robustness used techniques and skills to achieve COD, resulting in superior COD performance with a puck compared to stronger athletes. CODs with and without a puck are discrete skills requiring different abilities.
Keywords: sports training; agility; motor abilities; Illinois agility; skeletal muscle